Spatio-temporal variation of Scleractinian coral recruitment on terra-cotta tiles and artificial live rock in Tioman Island, Malaysia - Muhammad Hanafiah, Muhammad Faiz; Saad, Shahbudin; Mukai, Yukinori (2013)
Coral recruitment is a vital natural process in shaping the overall dynamic and spatio-temporal patchiness in coral assemblages. Spatio-temporal coral recruitment pattern on terra-cotta tiles and artificial live rock settlement plates were investigated between April 2012 and September 2012 at four locations in Tioman Island, Malaysia namely Kg Genting, PuJau Renggis, Teluk Teduh and Teluk Juara. Coral recruits were categorized as Acropora, Montipora, Pocillopora, Stylophora and Fungia respectively. A total of 879 coral recruits were recorded and Acropora dominated with 69.7%, followed by Pocillopora (17.3%), Stylophora (10.7%), Montipora (2.2%) and Fungia (0.01%). Kruskal-Wallis ANOVA was used to examine differences in coral recruitment among sites and types of settlement plates. There were significant differences in the abundance of Acropora, Montipora and Pocillopora recruits among sites (p < 0.05). However, significant differences were observed only in Pocillopora and Stylophora recruits among types of settlement plates used.